Custos e margens de comercialização de insumos agropecuários na Zona da Mata de Minas Gerais - da Silva, Aylzio José; Leitão e Silva, Josué; Teixeira Filho, A R; Fagundes de Sousa, A (Revista Ceres, 2025)
The problem of "technological backwardness" in the Zona da Mata of Minas Gerais was studied within a frame of reference that is not frequently used by agricultural economists. In order to better understand the current level of technology, the marginal and the operating costs of the retailers for modern agricultural inputs were analyzed, seeking to evaluate the performance efficiency in this stage of the marketing process.